Mix-and-match Implantation of Multifocal and Extended Depth of Focus IOLs - K. B. Pershin; N. F. Pashinova; А. Yu. Tsygankov; E. A. Antonov; I. V. Kosova; L. V. Batalina (Oftalʹmologiâ)
Purpose: Analysis of results of combined implantation of nondiffractive IOL with extended depth of focus and multifocal IOL.Materials and methods. The study included 40 patients (80 eyes) after cataract phacoemulsification or clear lens removal with a mean followup of 15.4 ± 1.2 (12–22) months. Women accounted for 60 % (n = 24) and men for 40 % (n = 16). 20 patients (40 eyes) with bilateral AcrySof IQ Vivity implantation formed the minimonovision group (group I), and 20 patients (40 eyes) with AcrySof IQ Vivity implantation in the dominant eye (n = 20) and Acrysof IQ Panoptix implantation in the nondominant eye (n = 20) formed the group of mix-and-match implantation (group II).Results. At the maximum followup period of 3 months, UCNVA in group I was 0.61 ± 0.14, in group II — 0.82 ± 0.09 (p = 0.048), BCNVA — 0.66 ± 0.17 and 0.92 ± 0.14, respectively (p = 0.039). No significant differences were found between groups comparing UCIVA, BCIVA, UCDVA and BCDVA (p > 0.1), but slightly higher values were determined in patients after bilateral implantation of Acrysof IQ Vivity IOLs. In group I, 2 patients (10 %) had glare and 2 (10 %) had halo. Patients did not complain about difficulties in driving in the darkness. In 9 cases out of 20 (45 %) patients required spectacle correction for reading. In group II, adverse optical phenomena were identified in 7 patients (35 %), of which 4 patients (20 %) had glare and 3 (15 %) had halo. None of the patients required spectacle correction for reading. In both groups, 95 % of cases (19 patients) rated the surgical outcome as “excellent” and 5 % (1 patient) as “good”. Conclusion. For the first time in Russia, the results of combined (mix-andmatch) implantation of EDOF and trifocal IOLs in comparison with bilateral IOL implantation in presbyopic patients were analyzed. The advantage of combined implantation for achieving better near visual acuity and comparable incidence of adverse optical phenomena was shown.